1999
DOI: 10.1021/om9810246
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Metal Cluster Chemistry. 13. Syntheses and Isomer Distribution Studies of Cp2W2Ir2(μ-CO)3(CO)7-n(PR3)n(n= 1, 2; R = Ph, Me):  X-ray Crystal Structure of Cp2W2Ir2(μ-CO)3(CO)6(PPh3)

Abstract: Reactions of Cp2W2Ir2(CO)10 (1) with n equivalents of PPh3 and PMe3 (n = 1, 2) proceed in dichloromethane at room temperature to afford the clusters Cp2W2Ir2(μ-CO)3(CO)7 - n (PPh3) n (n = 1 (2), 2 (3)) and Cp2W2Ir2(μ-CO)3(CO)7 - n (PMe3) n (n = 1 (4), 2 (5)), respectively, in reasonable yields (38−63%). These products exhibit ligand fluxionality in solution, resolvable at low temperature into the constituent interconverting isomers. A structural study of one isomer of 2, namely 2a, reveals that the three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The clusters 13 − 15 have been characterized by a combination of IR and 1 H NMR spectroscopies, SI mass spectrometry, and satisfactory microanalysis ( 13 and 15 only), while the unstable product 16 has been characterized by IR and 1 H NMR spectroscopies only. The spectroscopic features of 13 − 16 are similar to those of their cyclopentadienyl analogues, , but extra bands are observed in the solution IR spectra of some examples.
3 .
…”
Section: Resultsmentioning
confidence: 74%
“…The clusters 13 − 15 have been characterized by a combination of IR and 1 H NMR spectroscopies, SI mass spectrometry, and satisfactory microanalysis ( 13 and 15 only), while the unstable product 16 has been characterized by IR and 1 H NMR spectroscopies only. The spectroscopic features of 13 − 16 are similar to those of their cyclopentadienyl analogues, , but extra bands are observed in the solution IR spectra of some examples.
3 .
…”
Section: Resultsmentioning
confidence: 74%
“…Transition-metal carbonyl cluster chemistry has been of enduring interest. , The redox properties of clusters have been of particular interest, clusters having been subjected to numerous detailed electrochemical studies. A natural extension to these studies is to link electroactive cluster modules through unsaturated bridges and utilize electrochemical techniques to assess electronic communication, but few examples of heterometallic clusters linked by unsaturated bridges exist, and until our recent report none had been examined electrochemically. As part of a detailed study of group 6−iridium mixed-metal cluster chemistry, we recently reported examples of cluster−alkyne adducts linked by phenylenevinylene bridges (Chart ) and their examination by cyclic voltammetry and UV−vis−near-IR spectroelectrochemistry . We have now expanded these studies to embrace bridging groups containing phenyleneethynylene units, the results from which are reported herein.…”
Section: Introductionmentioning
confidence: 95%
“…Few examples of heterometallic clusters linked by unsaturated bridges exist, and thus far none have been probed utilizing electrochemical techniques. We have been studying group 6−iridium clusters and have recently reported cluster-containing oligourethanes in which the cluster units are linked via saturated bridges …”
Section: Introductionmentioning
confidence: 99%